Curved Coordinate Systems: Coordinate Transformations and Jacobians
📂Mathematical Physics Curved Coordinate Systems: Coordinate Transformations and Jacobians The volume in a 3-dimensional Cartesian coordinate system is represented for any curvilinear coordinate system as follows.
d x d y d z = ∣ ∂ x ∂ q 1 ∂ y ∂ q 1 ∂ z ∂ q 1 ∂ x ∂ q 2 ∂ y ∂ q 2 ∂ z ∂ q 2 ∂ x ∂ q 3 ∂ y ∂ q 3 ∂ z ∂ q 3 ∣ d q 1 d q 2 d q 3 = ∣ ∂ x ∂ q 1 ∂ x ∂ q 2 ∂ x ∂ q 3 ∂ y ∂ q 1 ∂ y ∂ q 2 ∂ y ∂ q 3 ∂ z ∂ q 1 ∂ z ∂ q 2 ∂ z ∂ q 3 ∣ d q 1 d q 2 d q 3
dxdydz =\begin{vmatrix} \dfrac{ \partial x}{ \partial q_{1}} & \dfrac{ \partial y}{ \partial q_{1}} & \dfrac{ \partial z}{ \partial q_{1} }
\\[1em] \dfrac{ \partial x}{ \partial q_{2}} & \dfrac{ \partial y}{ \partial q_{2}} & \dfrac{ \partial z}{ \partial q_{2} }
\\[1em] \dfrac{ \partial x}{ \partial q_{3}} & \dfrac{ \partial y}{ \partial q_{3}} & \dfrac{ \partial z}{ \partial q_{3} } \end{vmatrix} dq_{1}dq_{2}dq_{3} = \begin{vmatrix}\dfrac{ \partial x}{ \partial q_{1}} & \dfrac{ \partial x}{ \partial q_{2}} & \dfrac{ \partial x}{ \partial q_{3}}
\\[1em] \dfrac{ \partial y}{ \partial q_{1}} & \dfrac{ \partial y}{ \partial q_{2}} & \dfrac{ \partial y}{ \partial q_{3}}
\\[1em] \dfrac{ \partial z}{ \partial q_{1}} & \dfrac{ \partial z}{ \partial q_{2}} & \dfrac{ \partial z}{ \partial q_{3}} \end{vmatrix}dq_{1}dq_{2}dq_{3}
d x d y d z = ∂ q 1 ∂ x ∂ q 2 ∂ x ∂ q 3 ∂ x ∂ q 1 ∂ y ∂ q 2 ∂ y ∂ q 3 ∂ y ∂ q 1 ∂ z ∂ q 2 ∂ z ∂ q 3 ∂ z d q 1 d q 2 d q 3 = ∂ q 1 ∂ x ∂ q 1 ∂ y ∂ q 1 ∂ z ∂ q 2 ∂ x ∂ q 2 ∂ y ∂ q 2 ∂ z ∂ q 3 ∂ x ∂ q 3 ∂ y ∂ q 3 ∂ z d q 1 d q 2 d q 3
Here, the determinant represented as a coefficient is called the Jacobian and is denoted as J J J . The Jacobian of each coordinate system is as follows.
Polar coordinate system:
J p o l a r = ∣ ∂ x ∂ r ∂ x ∂ θ ∂ y ∂ r ∂ y ∂ θ ∣ = r
J_{polar}=\begin{vmatrix}\dfrac{ \partial x}{ \partial r} & \dfrac{ \partial x}{ \partial \theta}
\\[1em] \dfrac{ \partial y}{ \partial r} & \dfrac{ \partial y}{ \partial \theta} \end{vmatrix}=r
J p o l a r = ∂ r ∂ x ∂ r ∂ y ∂ θ ∂ x ∂ θ ∂ y = r
Cylindrical coordinate system:
J c y l i n d e r i c a l = ∣ ∂ x ∂ ρ ∂ x ∂ ϕ ∂ x ∂ z ∂ y ∂ ρ ∂ y ∂ ϕ ∂ y ∂ z ∂ z ∂ ρ ∂ z ∂ ϕ ∂ z ∂ z ∣ = ρ
J_{cylinderical}= \begin{vmatrix}\dfrac{ \partial x}{ \partial \rho} & \dfrac{ \partial x}{ \partial \phi} & \dfrac{ \partial x}{ \partial z}
\\[1em] \dfrac{ \partial y}{ \partial \rho} & \dfrac{ \partial y}{ \partial \phi} & \dfrac{ \partial y}{ \partial z}
\\[1em] \dfrac{ \partial z}{ \partial \rho} & \dfrac{ \partial z}{ \partial \phi} & \dfrac{ \partial z}{ \partial z} \end{vmatrix}=\rho
J cy l in d er i c a l = ∂ ρ ∂ x ∂ ρ ∂ y ∂ ρ ∂ z ∂ ϕ ∂ x ∂ ϕ ∂ y ∂ ϕ ∂ z ∂ z ∂ x ∂ z ∂ y ∂ z ∂ z = ρ
Spherical coordinate system:
J s p h e r i c a l = ∣ ∂ x ∂ r ∂ x ∂ θ ∂ x ∂ ϕ ∂ y ∂ r ∂ y ∂ θ ∂ y ∂ ϕ ∂ z ∂ r ∂ z ∂ θ ∂ z ∂ ϕ ∣ = r 2 sin θ
J_{spherical}=\begin{vmatrix}\dfrac{ \partial x}{ \partial r} & \dfrac{ \partial x}{ \partial \theta} & \dfrac{ \partial x}{ \partial \phi}
\\[1em] \dfrac{ \partial y}{ \partial r} & \dfrac{ \partial y}{ \partial \theta} & \dfrac{ \partial y}{ \partial \phi}
\\[1em] \dfrac{ \partial z}{ \partial r} & \dfrac{ \partial z}{ \partial \theta} & \dfrac{ \partial z}{ \partial \phi} \end{vmatrix}=r^{2}\sin\theta
J s p h er i c a l = ∂ r ∂ x ∂ r ∂ y ∂ r ∂ z ∂ θ ∂ x ∂ θ ∂ y ∂ θ ∂ z ∂ ϕ ∂ x ∂ ϕ ∂ y ∂ ϕ ∂ z = r 2 sin θ
Proof
As shown above, when the position vector r \mathbf{r} r changes, the volume of the resulting parallelepiped is as follows.
d r x ⋅ ( d r y × d r z ) = d x d y d z
d\mathbf{r}_{x} \cdot (d\mathbf{r}_{y} \times d\mathbf{r}_{z})=dxdydz
d r x ⋅ ( d r y × d r z ) = d x d y d z
In the curvilinear coordinate system, let us say the change in the position vector r \mathbf{r} r when d r i d\mathbf{r}_{i} d r i changes to i i i component by d q i dq_{i} d q i .
d r = d r 1 + d r 2 + d r 3
d\mathbf{r}=d\mathbf{r}_{1}+d\mathbf{r}_{2}+d\mathbf{r}_{3}
d r = d r 1 + d r 2 + d r 3
Then, the volume of the parallelepiped formed by d r d\mathbf{r} d r remains unchanged, whether represented in Cartesian coordinates or any curvilinear coordinate system. In other words, the value of d r 1 ⋅ ( d r 2 × d r 3 ) d\mathbf{r}_{1}\cdot (d\mathbf{r}_{2}\times d\mathbf{r}_{3}) d r 1 ⋅ ( d r 2 × d r 3 ) remains constant regardless of the coordinate system, only the variables represent it change. If d q i dq_{i} d q i is a very small change, then it can be approximated as follows.
d r 1 = r ( q 1 + d q 1 , q 2 , q 3 ) − r ( q 1 , q 2 , q 3 ) = r ( q 1 + d q 1 , q 2 , q 3 ) − r ( q 1 , q 2 , q 3 ) d q 1 d q 1 = ∂ r ∂ q 1 d q 1 = ( ∂ x ∂ q 1 x ^ + ∂ y ∂ q 1 y ^ + ∂ z ∂ q 1 z ^ ) d q 1 d r 2 = ∂ r ∂ q 2 d q 2 = ( ∂ x ∂ q 2 x ^ + ∂ y ∂ q 2 y ^ + ∂ z ∂ q 2 z ^ ) d q 2 d r 3 = ∂ r ∂ q 3 d q 3 = ( ∂ x ∂ q 3 x ^ + ∂ y ∂ q 3 y ^ + ∂ z ∂ q 3 z ^ ) d q 3
\begin{align*}
d\mathbf{r}_{1} &= \mathbf{r}(q_{1}+dq_{1},q_{2},q_{3})-\mathbf{r}(q_{1},q_{2},q_{3})
\\[1em] &=\dfrac{ \mathbf{r}(q_{1}+dq_{1},q_{2},q_{3})-\mathbf{r}(q_{1},q_{2},q_{3})}{ d q_{1} }dq_{1}
\\[1em] &= \dfrac{ \partial \mathbf{r}}{ \partial q_{1} }dq_{1}=\left( \dfrac{ \partial x}{ \partial q_{1}}\hat{\mathbf{x}}+\dfrac{ \partial y}{ \partial q_{1}}\hat{\mathbf{y}}+\dfrac{ \partial z}{ \partial q_{1} }\hat{\mathbf{z}} \right)dq_{1}
\\[1em] d\mathbf{r}_{2} &= \dfrac{ \partial \mathbf{r}}{ \partial q_{2} }dq_{2}=\left( \dfrac{ \partial x}{ \partial q_{2}}\hat{\mathbf{x}}+\dfrac{ \partial y}{ \partial q_{2}}\hat{\mathbf{y}}+\dfrac{ \partial z}{ \partial q_{2} }\hat{\mathbf{z}} \right)dq_{2}
\\[1em] d\mathbf{r}_{3} &= \dfrac{ \partial \mathbf{r}}{ \partial q_{3}}dq_{3}=\left( \dfrac{ \partial x}{ \partial q_{3}}\hat{\mathbf{x}}+\dfrac{ \partial y}{ \partial q_{3}}\hat{\mathbf{y}}+\dfrac{ \partial z}{ \partial q_{3} }\hat{\mathbf{z}} \right)dq_{3}
\end{align*}
d r 1 d r 2 d r 3 = r ( q 1 + d q 1 , q 2 , q 3 ) − r ( q 1 , q 2 , q 3 ) = d q 1 r ( q 1 + d q 1 , q 2 , q 3 ) − r ( q 1 , q 2 , q 3 ) d q 1 = ∂ q 1 ∂ r d q 1 = ( ∂ q 1 ∂ x x ^ + ∂ q 1 ∂ y y ^ + ∂ q 1 ∂ z z ^ ) d q 1 = ∂ q 2 ∂ r d q 2 = ( ∂ q 2 ∂ x x ^ + ∂ q 2 ∂ y y ^ + ∂ q 2 ∂ z z ^ ) d q 2 = ∂ q 3 ∂ r d q 3 = ( ∂ q 3 ∂ x x ^ + ∂ q 3 ∂ y y ^ + ∂ q 3 ∂ z z ^ ) d q 3
Therefore, the volume is calculated as follows.
d r 1 ⋅ ( d r 2 × d r 3 ) = ( ∂ r ∂ q 1 d q 1 ) ⋅ ( ∂ r ∂ q 2 d q 2 × ∂ r ∂ q 3 d q 3 ) = ( ∂ r ∂ q 1 ) ⋅ ( ∂ r ∂ q 2 × ∂ r ∂ q 3 ) d q 1 d q 2 d q 3 = ∣ ∂ x ∂ q 1 ∂ y ∂ q 1 ∂ z ∂ q 1 ∂ x ∂ q 2 ∂ y ∂ q 2 ∂ z ∂ q 2 ∂ x ∂ q 3 ∂ y ∂ q 3 ∂ z ∂ q 3 ∣ d q 1 d q 2 d q 3
\begin{align*}
d\mathbf{r}_{1} \cdot (d\mathbf{r}_{2}\times d\mathbf{r}_{3}) &= \left( \dfrac{ \partial \mathbf{r}}{ \partial q_{1}}dq_{1} \right)\cdot \left( \dfrac{ \partial \mathbf{r}}{ \partial q_{2}}dq_{2}\times \dfrac{ \partial \mathbf{r}}{ \partial q_{3}}dq_{3}\right)
\\[1em] &= \left( \dfrac{ \partial \mathbf{r}}{ \partial q_{1}} \right)\cdot \left( \dfrac{ \partial \mathbf{r}}{ \partial q_{2}}\times \dfrac{ \partial \mathbf{r}}{ \partial q_{3}}\right)dq_{1}dq_{2}dq_{3}
\\[1em] &= \begin{vmatrix} \dfrac{ \partial x}{ \partial q_{1}} & \dfrac{ \partial y}{ \partial q_{1}} & \dfrac{ \partial z}{ \partial q_{1} }
\\[1em] \dfrac{ \partial x}{ \partial q_{2}} & \dfrac{ \partial y}{ \partial q_{2}} & \dfrac{ \partial z}{ \partial q_{2} }
\\[1em] \dfrac{ \partial x}{ \partial q_{3}} & \dfrac{ \partial y}{ \partial q_{3}} & \dfrac{ \partial z}{ \partial q_{3} } \end{vmatrix} dq_{1}dq_{2}dq_{3}
\end{align*}
d r 1 ⋅ ( d r 2 × d r 3 ) = ( ∂ q 1 ∂ r d q 1 ) ⋅ ( ∂ q 2 ∂ r d q 2 × ∂ q 3 ∂ r d q 3 ) = ( ∂ q 1 ∂ r ) ⋅ ( ∂ q 2 ∂ r × ∂ q 3 ∂ r ) d q 1 d q 2 d q 3 = ∂ q 1 ∂ x ∂ q 2 ∂ x ∂ q 3 ∂ x ∂ q 1 ∂ y ∂ q 2 ∂ y ∂ q 3 ∂ y ∂ q 1 ∂ z ∂ q 2 ∂ z ∂ q 3 ∂ z d q 1 d q 2 d q 3
For any matrix A A A , since ∣ A T ∣ = ∣ A ∣ \left| A^{T} \right| =\left| A \right| A T = ∣ A ∣ , the following is obtained.
d x d y d z = ∣ ∂ x ∂ q 1 ∂ y ∂ q 1 ∂ z ∂ q 1 ∂ x ∂ q 2 ∂ y ∂ q 2 ∂ z ∂ q 2 ∂ x ∂ q 3 ∂ y ∂ q 3 ∂ z ∂ q 3 ∣ d q 1 d q 2 d q 3 = ∣ ∂ x ∂ q 1 ∂ x ∂ q 2 ∂ x ∂ q 3 ∂ y ∂ q 1 ∂ y ∂ q 2 ∂ y ∂ q 3 ∂ z ∂ q 1 ∂ z ∂ q 2 ∂ z ∂ q 3 ∣ d q 1 d q 2 d q 3
\begin{align*}
dxdydz &=\begin{vmatrix} \dfrac{ \partial x}{ \partial q_{1}} & \dfrac{ \partial y}{ \partial q_{1}} & \dfrac{ \partial z}{ \partial q_{1} }
\\[1em] \dfrac{ \partial x}{ \partial q_{2}} & \dfrac{ \partial y}{ \partial q_{2}} & \dfrac{ \partial z}{ \partial q_{2} }
\\[1em] \dfrac{ \partial x}{ \partial q_{3}} & \dfrac{ \partial y}{ \partial q_{3}} & \dfrac{ \partial z}{ \partial q_{3} } \end{vmatrix} dq_{1}dq_{2}dq_{3}
\\[1em] &= \begin{vmatrix}\dfrac{ \partial x}{ \partial q_{1}} & \dfrac{ \partial x}{ \partial q_{2}} & \dfrac{ \partial x}{ \partial q_{3}}
\\[1em] \dfrac{ \partial y}{ \partial q_{1}} & \dfrac{ \partial y}{ \partial q_{2}} & \dfrac{ \partial y}{ \partial q_{3}}
\\[1em] \dfrac{ \partial z}{ \partial q_{1}} & \dfrac{ \partial z}{ \partial q_{2}} & \dfrac{ \partial z}{ \partial q_{3}} \end{vmatrix}dq_{1}dq_{2}dq_{3}
\end{align*}
d x d y d z = ∂ q 1 ∂ x ∂ q 2 ∂ x ∂ q 3 ∂ x ∂ q 1 ∂ y ∂ q 2 ∂ y ∂ q 3 ∂ y ∂ q 1 ∂ z ∂ q 2 ∂ z ∂ q 3 ∂ z d q 1 d q 2 d q 3 = ∂ q 1 ∂ x ∂ q 1 ∂ y ∂ q 1 ∂ z ∂ q 2 ∂ x ∂ q 2 ∂ y ∂ q 2 ∂ z ∂ q 3 ∂ x ∂ q 3 ∂ y ∂ q 3 ∂ z d q 1 d q 2 d q 3
■